Efektivitas Model Pembelajaran Kooperatif Tipe Think-Pair-Share terhadap Hasil Belajar Matematika Materi SPLDV di SMA - Sianturi, Putri Rahayu; Hidayati, Ully; Nasruddin, Nasruddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the differences in mathematics learning outcomes between students who follow learning with the TPS model and students who follow conventional learning. This study uses a quantitative approach with a quasi-experimental design of the posttest only control group design. The research subjects were 59 students consisting of 31 students in the experimental class and 28 students in the control class. The experimental class received learning with the TPS model and the control class used conventional learning methods. Data were collected through learning outcome tests. Data analysis was carried out using normality tests, homogeneity tests, and independent sample t-tests at a significance level of 0.05. The results showed that the average learning outcomes of the experimental class were 89.39% while the control class was 62.04%. The t-test results showed a significance value = 0.000˂0.05, so there was a significant difference between the two classes. Thus, this study shows a significant difference in mathematics learning outcomes between students who received learning with the TPS model and students who learned conventionally, where the experimental class obtained higher results than the control class. Keywords: Think-Pair-Share (TPS), Mathematics, System of Linear Equastion in Two Variabels (SPLDV).